2015
DOI: 10.1155/2015/959402
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hydrogen Transport in Flexible‐Wall Narrow Carbon Nanotubes

Abstract: Understanding the interaction between hydrogen and carbon nanotubes is crucial to enhancing the performance of hydrogen storage and nanofluidic carbon-adsorbent systems. Accordingly, this study performs a series of molecular dynamics simulations to investigate the transport properties of hydrogen molecules confined within a flexible narrow carbon nanotube. The tube's diameter is 10.8Å at temperatures in the range of 100∼800 K. The particle loadings inside carbon nanotubes are ranging from 0.01∼1 No/Å. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In another work, Chen et al (2014) performed a series of MD simulations to investigate the transport properties of hydrogen molecules confined within flexible narrow CNTs. They showed that the hydrogen molecules exhibit three distinct diffusion regimes, namely single-file, Fickian, and ballistic, depending on the value of the Knudsen number.…”
Section: Separation Of Gaseous Mixtures Using Carbonbased Nanomateriamentioning
confidence: 99%
“…In another work, Chen et al (2014) performed a series of MD simulations to investigate the transport properties of hydrogen molecules confined within flexible narrow CNTs. They showed that the hydrogen molecules exhibit three distinct diffusion regimes, namely single-file, Fickian, and ballistic, depending on the value of the Knudsen number.…”
Section: Separation Of Gaseous Mixtures Using Carbonbased Nanomateriamentioning
confidence: 99%
“…In [14], the effect of superdiffusion of propane transport in open CNTs is demonstrated by the molecular dynamics method. As it was shown in [16], the hydrogen transfer regime depends on both the pore diameter and the particle loading and changes from single-file diffusion to ballistic.…”
Section: Introductionmentioning
confidence: 77%
“…Then the regime of particle transfer will be determined both by their collisions with the CNT walls, and by directional particle jumps between collisions, which should lead to a faster regime of particle transfer. Similar considerations regarding the change in the transport regime upon collision with CNT walls are given, for example, in [14] and [16] -in terms of Knudsen number. In [14], the effect of superdiffusion of propane transport in open CNTs is demonstrated by the molecular dynamics method.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…From the above, the carbon nanotube has potential applications in gas transportation and gas storage [15][16][17][18]. In practice, the carbon nanotube samples may have nanopores due to various point defects [19].…”
Section: Introductionmentioning
confidence: 99%